2020
DOI: 10.3399/bjgp.2020.0750
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing community-acquired pneumonia via a smartphone-based algorithm: a prospective cohort study in primary and acute-care consultations

Abstract: Background: Community-acquired pneumonia (CAP) is an essential consideration in patients presenting to primary care with respiratory symptoms; however, accurate diagnosis is difficult when clinical and radiologic examinations are not possible, such as during telehealth consultations. Aim: To develop and test a smartphone-based algorithm for diagnosing CAP without need for clinical examination or radiology inputs. Design and Setting: A prospective cohort study using data from subjects aged over 12 years present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This approach, however, relies on the quality and generalizability of the training data sets and can only be used after all information has been entered into the patient's medical record. Studies of algorithms that use point-of-care automated cough-centered analysis have reported good diagnostic accuracy for respiratory diseases, including pneumonia, correctly identifying 87% of children and 86% of adults without the need for clinical examination or investigations (49)(50)(51)(52). In settings with limited resources, such algorithms might provide a diagnostic method equal to the accuracy of well-resourced E.D.s.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, however, relies on the quality and generalizability of the training data sets and can only be used after all information has been entered into the patient's medical record. Studies of algorithms that use point-of-care automated cough-centered analysis have reported good diagnostic accuracy for respiratory diseases, including pneumonia, correctly identifying 87% of children and 86% of adults without the need for clinical examination or investigations (49)(50)(51)(52). In settings with limited resources, such algorithms might provide a diagnostic method equal to the accuracy of well-resourced E.D.s.…”
Section: Discussionmentioning
confidence: 99%
“…This approach, however, relies on the quality and generalizability of the training data sets and can only be used after all information has been entered into the patient's medical record. Studies of algorithms that use point-of-care automated cough-centered analysis have reported good diagnostic accuracy for respiratory diseases, including pneumonia, correctly identifying 87% of children and 86% of adults without the need for clinical examination or investigations (49)(50)(51)(52). In settings with limited resources, such algorithms might provide a diagnostic method equal to the accuracy of wellresourced E.D.s.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas past studies on automatic detection of cough sounds required the use of heavy equipment, recent advancements in digital devices and the rise in telehealth demand with the COVID-19 pandemic [ 4 , 6 , 7 ] have facilitated the capabilities of mobile devices to record cough sounds successfully. New techniques can extract features that can be applied to algorithms for diagnosis [ 5 ], or community-acquired pneumonia [ 1 ]. Our two cases are the first to rely on digital devices to record acoustic cough sounds in aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, pneumonia is the most common cause of infectious mortality, with more than two million adults dying from lower respiratory infections [ 1 ]. Previously collected data indicate that 60% of community-acquired pneumonia patients and 87% of hospital-acquired pneumonia patients are diagnosed with aspiration pneumonia [ 2 ].…”
Section: Introductionmentioning
confidence: 99%